A rare case of metastatic extramammary Paget disease of the spine and review of the literature - Ahmed, A. Karim (J Clin Neurosci, 2017)
Extramammary Paget disease is an intraepithelial neoplasm affecting cells rich in apocrine glands-often located in the vulvar, scrotal, or perianal region. It typically affects older patients, between the ages of 50 and 80 years old, and is most often limited to the epidermis. A 47-year-old Asian male first presented with enlargement of the right inguinal lymph node. A subsequent biopsy revealed extrammamary Paget disease of the scrotum. The patient eventually developed significant worsening back pain with bilateral lower extremity numbness and weakness three months later. Imaging demonstrated a pathologic compression fracture of the L4 vertebral body with metastatic epidural spinal cord compression. The patient underwent surgical decompression of the spine with bilateral L4 laminectomy, resection of epidural tumor, and pedicle screw fixation from L2 to S1. Surgical pathology demonstrated metastatic adenocarcinoma consistent with extramammary Paget disease. Although two other case reports have described spinal metastases from extramammary Paget disease, to the author’s knowledge, this represents the first report of surgical decompression and fusion for extramammary Paget disease of the spine.